Stretchable multifunctional hydrogels for sensing electronics with effective EMI shielding properties. Issue 40 (28th September 2021) - Hao, Mingming; Wang, Yongfeng; Li, Lianhui; Lu, Qifeng; Sun, Fuqin; Li, Lili; Yang, Xianqing; Li, Yue; Liu, Mengyuan; Feng, Sijia; Feng, Simin; Zhang, Ting
Abstract : The magnetic-field-induced method is employed to develop a multifunctional hydrogel with fast response and outstanding EMI shielding effectiveness for fabrication of wearable sensors. Abstract : Hydrogel-based soft and stretchable materials with skin/tissue-like mechanical properties provide new avenues for the design and fabrication of wearable sensors. However, synthesizing multifunctional hydrogels that simultaneously possess excellent mechanical, electrical and electromagnetic interference (EMI) shielding effectiveness is still a great challenge. In this work, the freeze-casting method is employed to fabricate a multifunctional hydrogel by filling Fe3 O4 clusters into poly(3, 4-ethylenedioxythiophene)-poly(styrene sulfonic acid) (PEDOT:PSS) and polyvinyl alcohol (PVA) composite aqueous solution. The hydrogel possesses superior electrical and mechanical properties as well as great electromagnetic wave shielding properties. Benefiting from the high stretchability (∼904.5%) and fast sensing performance (response time ∼9 ms and self-recovery time ∼12 ms within the strain range ∼100%), the monitoring of human activities and manipulation of a remote-controlled toy car using the hydrogel-based stretchable strain sensors are successfully demonstrated. In addition, a great EMI shielding effectiveness with more than 46 dB in the frequencies of 8–12.5 GHz can be obtained, which provides an alternative strategy for designing next-generation EMI shielding materials. These results indicate that the multifunctional hydrogels can be used as flexible and stretchable sensing electronics requiring effective EMI shielding.